Assessment of demographic attributes and health profile of schedule caste of 5 villages of Aligarh District, Uttar Pradesh, India - Akhtar, Sada; Mudassir, Mohd; Faiz, Abul; Khan, Parvez; Afza, Sheereen; Ahmad, Farha; Ahmad, N. Zaheer (International Journal Of Community Medicine And Public Health, 2024)
Background: Demography is the scientific study of human populations. It takes into account the quantitative aspects of their general characteristics. In this paper health profile and different attributes of demography like age, gender, caste, marital status, educational status, temperament and occupation etc of scheduled caste people of 5 villages of Aligarh district were assessed and documented. Methods: A pretested, predesigned questionnaire containing the demographic attributes was filled by researchers by face-to-face examination of the population through scheduled caste sub plan mobile health care OPD’s. Surveys were conducted from 2nd June to 25th September 2022. Results: Collected and analyzed data exhibits that there were marked difference with the age groups 0-15, 26-45 and 66-85, gender, caste, with religion of Hindu (90.83%) and Muslim (7.33%), educational status regarding illiterate (59.81) and graduate or above (1.65%), Mizaj, dietary habit and there were no significant differences regarding marital status, occupation and addiction behavior were noticed. Conclusions: It can be concluded that majority of the scheduled caste population was living in interiors of rural areas with low socio-economic and health status. Most visited gender were females which indicate poor nutrition, lack of immunity and excessive burden on them. Majority of the population belongs to Balghami Mizaj. Most preferred diets were mixed and main occupation of the scheduled caste population was agriculture. This study will make policy makers and health workers derive practical conclusions which will help in the upliftment of the scheduled caste populations.